Transformasi Pola Pikir Masyarakat Desa Saringembat terhadap Kebersihan Lingkungan: Dari Kesadaran Hingga Aksi - Ratu Ajeng Pratiwi; Yanda Bara Kusuma (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines the transformation of the mindset of the people of Saringembat Village concerning environmental cleanliness, from the stage of awareness to concrete actions. Saringembat Village, which previously faced challenges in managing environmental cleanliness, has shown significant changes in the views and behavior of its residents after implementing several community work programs and public participation. The research method used is a qualitative approach with data collection techniques through interviews and observations. The results of the study indicate that the main driving factors for this transformation are continuous training, the involvement of community leaders, and support from external actors such as the government and NGOs. This change is reflected in the growing individual awareness of the importance of cleanliness, better waste management, and active community participation in regular cleanliness activities.